Ivanhoe - Scott, Walter, Sir, 1771-1832 ([Boston, Mass] : Thomson Heinle, 2005)
An abridgment of the novel chronicling the adventures of the Saxon knight Ivanhoe in 1194, the year of Richard the Lion-Hearted's return from the Third Crusade
Title from container
Keywords: Ivanhoe, Wilfred of, Sir (Fictitious character) -- Fiction; Triangles (Interpersonal relations) -- Fiction; Normans -- Great Britain -- Fiction; Knights and knighthood -- Fiction; Jews -- Great Britain -- Fiction